Lipid Biomarker and Isotopic Study of Community Distribution and Biomarker Preservation in a Laminated Microbial Mat from Shark Bay, Western Australia - Pages, Anais; Grice, Kliti; Welsh, D.; Teasdale, P.; Van Kranendonk, M.; Greenwood, Paul (Wiley-Blackwell Publishing, 2015)
Modern microbial mats from Shark Bay present some structural similarities with ancient stromatolites; thus, the functionality of microbial communities and processes of diagenetic preservation of modern mats may provide an insight into ancient microbial assemblages and preservation. In this study, the vertical distribution of microbial communities was investigated in a well-laminated smooth mat from Shark Bay. Biolipid and compound-specific isotopic analyses were performed to investigate the distribution of microbial communities in four distinct layers of the mat. Biomarkers indicative of cyanobacteria were more abundant in the uppermost oxic layer. Diatom markers (e.g. C25 HBI alkene, C20:4ω6 and C20:5ω3 polar lipid fatty acids (PLFAs)) were also detected in high abundance in the uppermost layer, but also in the deepest layer under conditions of permanent darkness and anoxia, where they probably used NO3 − for respiration. CycC19:0, an abundant PLFA of purple sulfur bacteria (PSB), was detected in all layers and presented the most 13C-depleted values of all PLFAs, consistent with photoautotrophic PSB. Sulfur-bound aliphatic and aromatic biomarkers were detected in all layers, highlighting the occurrence of early sulfurisation which may be an important mechanism in the sedimentary preservation of functional biolipids in living and, thus, also ancient mats.